EFFECT OF BLANCHING AND DRYING PROCESS ANALYSIS OF CABYA FRUIT (Piper retrofractrum Vahl.) USING SOLAR DRYER - Amirada Nur Laily; La Choviya Hawa; Sandra Malin Sutan (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
One of the dried products that commonly used in Indonesia is cabya fruits (Piper retrofractum Vahl.). Cabya fruits usually used as seasoning and folk medicine that have various benefits for health. Solar dryer is an option that can be used as one of post-harvest handling. Drying rate, mathematical modeling of drying curve and physical characteristic as parameters to develop the drying process of cabya fruit using solar dryer have been studied. The effect of water blanching pretreatment also investigated. The final average moisture content of nontreatment and blanching cabya fruit were 9.34±0.56 and 9.70±1.1, respectively. The fruit with blanching pretreatment decrease moisture content faster than nontreatment cabya fruit. The drying rate of cabya fruit decreased with increasing the drying time and reducing the moisture content. Mathematical modelling in this research predicted according to the criteria of statistical parameters, i.e., the greatest of R2 value and the smallest of χ2 and RMSE value. The fittest model in this research was Midilli et. al. Cabya fruit with blanching pretreatment had less shrinkage than nontreatment cabya fruit.